Project little light - Nur Haidah Binte Mohamed Arip (Nanyang Technological University, 2024)
Fuelled by the need for social support and self-understanding in the navigation of young adult existentialism, Project Little Light hopes to encourage vulnerability and human connection through a four-part illustrated book series. By using design and visual metaphors as a medium of communication and connection, these books follow a semi-non-linear narrative and speak from a personal voice of vulnerability – with the aim of highlighting the process of unpacking and understanding the emotions of the past from childhood and teenage-hood.